2008
DOI: 10.1002/cjce.5450830307
|View full text |Cite
|
Sign up to set email alerts
|

Wall Effects in Two-Dimensional Axisymmetric Flow Over a Circular Disk Oriented Normal to Flow in a Cylindrical Tube

Abstract: T he presence of fi nite boundaries is known to exert an extra retardation force on freely settling objects. Conversely, the terminal falling velocity of a solid particle is known to be lower in the presence of fi nite boundaries than that in an unconfi ned medium but otherwise under identical conditions. Qualitatively speaking, the extra retardation effect arises from the upward fl ow of the liquid, and obviously closer are the walls to the falling object, stronger is the upward fl ux and more severe is the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…This qualitative inference is also in line with the subsequent experimental findings of Chhabra et al [23] and Rami et al [24]. Both Chhabra et al [23] and Rami et al [24] concluded that the drag coefficient of disks in power law fluids was in line with the corresponding expression for drag in Newtonian liquids [4,16,25]. Combined, these results embrace the following ranges of conditions: Re 100 and power law index from 0.48 to 1.…”
Section: Previous Worksupporting
confidence: 91%
See 4 more Smart Citations
“…This qualitative inference is also in line with the subsequent experimental findings of Chhabra et al [23] and Rami et al [24]. Both Chhabra et al [23] and Rami et al [24] concluded that the drag coefficient of disks in power law fluids was in line with the corresponding expression for drag in Newtonian liquids [4,16,25]. Combined, these results embrace the following ranges of conditions: Re 100 and power law index from 0.48 to 1.…”
Section: Previous Worksupporting
confidence: 91%
“…3) for the Newtonian fluids [4] in the range 1 < Re < 100 and 0.48 n 0.79. The following equation [4] appears to consolidate the experimental and numerical results [16,25] for circular disks settling in Newtonian fluids, in the absence of wall effects, i.e., e = 0: The good correspondence seen in Fig. 3 is primarily due to the fact that the total drag is dominated by the pressure component and this is little influenced by the shear thinning behavior of the liquid.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations